Evaluation of Body Weight, Morphometry, and Physiology Status of Etawah Crossbred Doeling on Two Different Farms Management - Nur Laili Ma'rufah; Tridjoko Wisnu Murti; Budi Prasetyo Widyobroto; Sulvia Dwi Astuti (Faculty of Animal Science, Universitas Gadjah Mada, 2023)
This study aimed to evaluate the body weight (BW), morphometry, and physiological status of Etawah Crossbred Doeling (ECD) under different farms management. This study was performed in two farms, Garage (Tlogoadi village, Mlati subdistrict) and Bumiku Hijau (Margomulyo village, Seyegan subdistrict), both located in Yogyakarta and each farm used 6 ECD as the replications (12 animals in total). Parameters of the study consist of body weight (BW), morphometry (chest girth, hip height, body length, chest depth, ear length, ear width, and withers height), physiological status (respiration, pulse, and rectal temperature). The parameter was measured weekly for four consecutive weeks of observation. The results showed that the difference in farm management between Garage and Bumiku Hijau influenced on the BW, morphometry, and physiological status of ECD. The study showed that the BW and all morphometry from the Garage farm was higher than Bumiku Hijau farm (P<0.05). However, the physiological status (except for rectal temperature) from Garage farm was lower than Bumiku Hijau farm (P<0.05). It can be concluded that Garage farm implemented better good farming practices compared to Bumiku Hijau farm.